Reestruturação produtiva e qualificação profissional: história, caminhos e o papel da educação no Banco do Brasil - Bezerra, Ari Feijó (2006)
In this work we try to treat, inside of the subject professional qualification, the role of the education in the state-owned company “Banco do Brasil”, face to the reorganizations of the capital, from the transistion of the military dictatorship until the present time. The professional formation, inside of the education, englobe the processes that allow the human being to acquire and to develop knowledge that involve theories and techniques related to the production of goods and services, independent of this process to happen in the schools or the companies. The Brazilian professional education is organized parallel to the school system and encloses, beyond the preparation for the work market, the proper formation of the worker for the exercise of its functions in the work environment. Facing the changes of the capital, from the economic opening and of the presidential successions that determine the nomination in the state and ministries, we made a research of the role of the education in this company of mixing economy - however taking care of to the public yearnings of citizens (government, customers and employees), together with the private necessities of its customers and shareholders.